Experimental Study on the Influence of Stand-Off of Directional Measurement While Drilling (MWD) Instrument With Barrel - Wang, Zhiming; Pan, Feifan; Pan, Yufei; Tian, Bohui (Recent Patents on Engineering, 2024)
<span class=
Keywords: Directional MWD instrument with barrel